O popular massivo: da mediação simbólica à trajetória do herói - Souza, Karlla Christine Araújo (2010)
The research is based on the literary job of four authors: Lourdes Ramalho, Jessier Quirino, Bráulio Tavares e Astier Basílio, extracting of their texts what symbolizes the resizing of the popular poetic language and of the oral tradition wich are linked. Their texts talk about customs and traditions and also try to recreate the storyline of the popular imaginary of Northeast. Even wich the difference between the authors, is exactly what is repeated that surprises us by the force of language and the reworking of some typical traits. Among these traits that are repeated and worked, is that we perceive the construction of heroes out of the conventional patterns of epic composition. They are heroes that do not have any big realization to boast themselves, therefore they hold up the courage to offer their own blood in the name of revenge that is, above all, fictional. This mechanism of compensation is also presented at the symbolical intention of their creators, wich linked to some characteristic traits of a regionalist script, are also associated with other elements, concerning to their actuation as symbolical mediators. What is the base of the symbolical mediation is the life observation, the interested by the tradition, the desire to validate the poetic forms that were learned at the familiar nucleus. Although, placing the mediation in the broader context of transformation of social processes, it implicitly incorporates the desire to reframe the forms of cultural domination. The symbolical mediation is the clipping of a local phenomenon between theoretical and cultural boundaries, a fresh approach to a practice that is not so new like that.